The relationship between energy consumption and industrial structure in Chinese provinces - Zoryna, Tatsiana G.; Xueyao, Liu (Journal of the Belarusian State University. Economics, 2022)
This paper analyses the situation of Chinese provinces in terms of energy consumption, industrial structure, and energy consumption structure. With the data of China and its various provinces, we apply grey relational analysis to study the relationship between energy consumption and industrial structure, and identify the magnitude of the impact of the different industries on energy consumption in each region. Corresponding optimisation measures are also proposed to each type of provinces.